Biliary Leak in Post-Liver-Transplant Patients: Is There Any Place for Metal Stent?. (24th April 2012) - Martins, Fernanda P.; Phillips, Melissa; Gaidhane, Monica R.; Schmitt, Timothy; Kahaleh, Michel
Abstract : Objectives . Endoscopic management of bile leak after orthotopic liver transplant (OLT) is widely accepted. Preliminary studies demonstrated encouraging results for covered self-expandable metal stents (CSEMS) in complex bile leaks. Methods . Thirty-one patients with post-OLT bile leaks underwent endoscopic temporary placement of CSEMS (3 partially CSEMS, 18 fully CSEMS with fins and 10 fully CSEMS with flare ends) between December 2003 and December 2010. Long-term clinical success and safety were evaluated. Results . Median stent indwelling and follow-up were 89 and 1, 353 days for PCSEMS, 102 and 849 for FCSEMS with fins and 98 and 203 for FCSEMS with flare ends. Clinical success was achieved in 100%, 77.8%, and 70%, respectively. Postplacement complications: cholangitis (1) and proximal migration (1), both in the FCSEMS with fins. Postremoval complications were biliary strictures requiring drainage: PCSEMS (1), FCSEMS with fins (6) and with flare ends (1). There was no significant differences in the FCSEMS groups regarding clinical success, age, gender, leak location, previous treatment, stent indwelling, and complications. Conclusion . Temporary placement of CSEMS is effective to treat post-OLT biliary leaks. However, a high number of post removal biliary strictures occurred especially in the FCSEMS with fins. CSEMS cannot be recommended in this patient population.